The critical role of ferritinophagy in human disease - Liu, Meng-Zhen; Kong, Ni; Zhang, Guang-Yu; Xu, Qin; Xu, Yang; Ke, Ping; Liu, Chong (Frontiers in Pharmacology, 2022)
Ferritinophagy is a type of autophagy mediated by nuclear receptor activator 4 (NCOA4), which plays a role in inducing ferroptosis by regulating iron homeostasis and producing reactive oxygen species in cells. Under physiological conditions, ferritinophagy maintains the stability of intracellular iron by regulating the release of free iron. Studies have demonstrated that ferritinophagy is necessary to induce ferroptosis; however, under pathological conditions, excessive ferritinophagy results in the release of free iron in large quantities, which leads to lipid peroxidation and iron-dependent cell death, known as ferroptosis. Ferritinophagy has become an area of interest in recent years. We here in review the mechanism of ferritinophagy and its association with ferroptosis and various diseases to provide a reference for future clinical and scientific studies.